An essential role of disulfide bonds for the hierarchical self-assembly and underwater affinity of CP20-derived peptides - Li, Baoshan; Song, Junyi; Mao, Ting; Zeng, Ling; Ye, Zonghuang; Hu, Biru (Frontiers in Bioengineering and Biotechnology, 2022)
Barnacles are typical fouling organisms strongly adhering to immersed solid substrates by secreting proteinaceous adhesives, called cement proteins (CPs). The self-assembly of the cement proteins forms a permanently bonded layer that binds barnacles to foreign surfaces. However, it is difficult to determine their natural structure and describe their self-assembly properties due to the abundance of cysteines in whole-length CP20. A putative functional motif of Balanus albicostatus CP20 (BalCP20) was identified to present distinctive self-assembly and wet-adhesion characteristics. The atomic force microscopy (AFM) and transmission electron microscope (TEM) investigations showed that wildtype BalCP20-P3 formed grain-like spindles, which assembled into fractal-like structures like ears of wheat. SDS-PAGE, AFM, and LSCM showed that DTT treatment opened up disulfide bonds between cysteines and disrupted the fractal-like structures. Additionally, these morphologies were abolished when one of the BalCP20-P3 four cysteines was mutated by alanine. Circular dichroism (CD) results suggested that the morphological diversity among BalCP20-P3 and its mutations laid on the proportion of α-helix. Finally, quartz crystal microbalance with dissipation (QCM-D) detected that BalCP20-P3 and its mutations with diverse self-assemblies occupied different wet adhesions. The above results demonstrated that cysteines and disulfide bonds played a crucial role in the self-assembly and wet adhesion of BalCP20-P3. The work provides new insights into underwater adhesions of BalCP20 and a novel bionic underwater adhesive.